The language use of the Balinese diaspora in Kampung Bali, Penganjuran, a multilingual village in Banyuwangi - Nurhayani, Ika; Sahiruddin, Sahiruddin; Junining, Esti; Hamamah, Hamamah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
The paper investigates the language use of the Balinese diaspora in Kampung Bali, Penganjuran, a multilingual village in Banyuwangi, which includes the multilingual situation, the nature of the language accommodation and the language domains. The current study answers the following research questions: (1) how is the situation of multilingualism in the village? (2) how is the situation of language accommodation in the Balinese village in the village? and (3) what are the domains of the use of the languages spoken in the village? The research applied a qualitative research approach using semi-structured interviews. Thirteen questions were asked during the interviews with three research participants. The answers were coded into data related to multilingualism situation, language accommodation, and domains of language use of the languages spoken in Kampung Bali, Penganjuran. The analysis aims to search for patterns and links in the coded texts. The findings show that the Balinese diaspora is the most multilingual ethnic group in Kampung Bali, Penganjuran, as they speak five languages: Indonesian, Balinese, Osing, Javanese, and Madurese. The Balinese also displays an accommodative nature toward the national language and the dominant vernacular languages. The findings also show that the domains of use of Balinese in the diaspora have declined since it is only used at the house of worship by three research participants and at home by one participant. The accommodative nature of the Balinese diaspora might have contributed to the shift from Balinese to the national language or to the dominant vernacular languages.